Construction and Implementation of a Digital System for Logistics Majors from the Perspective of Smart Education - Zuo, Lingqun; Xu, Chonghao; Wang, Shan; Li, Jisen (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: Faced with the new demand for logistics engineering talents in the modern logistics industry's mathematical transformation and upgrading, building an applied logistics engineering talent training system that meets the requirements of the new era is a key task of current teaching reform. Contribution: The contribution of this experiment is focuses on the current situation of school enterprise integration in school logistics engineering construction, and proposes a construction. Method:  This experiment using framework method to strengthen the logistics engineering profession, clarify integration goals, build targeted curriculum systems, establish assessment and evaluation frameworks, and improve the mechanism of industry education integration. Results: The collaborative educational role of logistics professional construction and innovation and entrepreneurship education and cultivate more comprehensive logistics professionals. Based on this, this article will conduct a digital system for logistics majors from the perspective of smart education in vocational colleges under the background of intelligent logistics. Conclusion: Curriculum construction is built on a dynamic and authentic practical process, which reflects the logical interaction between curriculum builders and courses, shifting understanding from project logic to subjective logic